DOMAIN SPECIFIC BELIEFS ABOUT WRITING AND WRITING PERFORMANCE OF PRESERVICE ENGLISH TEACHERS: IS THERE ANY RELATIONSHIP? - Seray Tanyer (Informascope, 2017)
Learning as a retrospective phenomenon can make learners transmit their past as an ingredient while they are (re)structuring their present and future. Previous and present experiences can form a basis for cognitive, behavioral and motivational factors which can create a cognitive load for learners and affect their learning process. In this regard, current study aims to investigate first-year undergraduates' beliefs about writing and relation of these beliefs to writing performance in essay writing. A total of 147 students studying in ELT department of a Turkish university participated in the research. Their domain-specific beliefs about writing were determined through the Beliefs about Writing Survey (BAWS). Writing performance was measured on an essay writing task by calculating both overall grade and six component grades. As a result, multiple regression analysis affirmed that beliefs about writing accounted for writing performance independently. Pearson correlation values showed that some beliefs about writing were adaptive and associated with higher writing scores (e.g. "Adapt to the Audience"). Also, some belief subcategories were associated with each other. The results of the present study have been discussed along with the related literature on beliefs about writing and writing performance. Implications/suggestions related to the coursework, writing practices and future research have been presented.